Biosynthesis of copper oxide nanoparticles using biomass, peel, and extract polysaccharides of Solanum Tuberosum for ultrasound‐assisted adsorption of azo direct red 80 contaminants. Issue 17 (1st September 2021) - Hamami, Zahra; Javanbakht, Vahid
Abstract: Bio-fabrication of nanomaterials using plant polysaccharides has recently attracted much scientific attention due to its low cost and simple operation. The green synthesis of copper oxide nanoparticles as adsorbent is performed for the removal of azo direct red 80 contaminants from aqueous solution with adsorption and ultrasonic-assisted adsorption processes. The biomass, peel, and extract polysaccharides of Solanum Tuberosum were applied as eco-friendly stabilizing agents to synthesize nanoparticles. The CuO nanoparticles were characterized using FESEM, XRD, BET, and antibacterial activity tests. The CuO nanoparticles biosynthesized from peel extract have better structural properties as compared to the nanoparticles prepared from biomass and extract of Solanum Tuberosum. The result showed that the average crystallite size of the CuO nanoparticles was about 25 nm with a specific surface area of 16.35 m 2 /g. The adsorption capacities of 13.09 and 14.07 mg/g were obtained for dye removal with the adsorption and ultrasonic-assisted adsorption processes. Adsorption process followed the pseudo-second-order kinetic model and the contribution of intra-particle diffusion was also observed. The adsorption potential of the nanoparticles in adsorption and ultrasonic-assisted adsorption processes was assessed for binary dye solution with synergetic effect. The CuO nanoparticle has shown its high regeneration ability even after 4 consecutive cycles of regeneration-reuse.